Xenogeneic lymphocytic RNA stimulates skeletal muscle regeneration - N. V. Tishevskaya; E. S. Golovneva; R. V. Gallyamutdinov; A. A. Pozina; N. M. Gevorkyan (Вестник трансплантологии и искусственных органов, 2021)
Objective: to find evidence of the existence of distant lymphocytic RNA control of physiological myogenesis as a way to control the muscle tissue regeneration process.Materials and methods. The study was conducted on male Wistar rats, n=33. In the first part of the experiment, 12 rats were subjected to regular 40-day physical activity (swimming), half of them were intraperitoneally injected 4 times with total RNA isolated from pig spleen lymphocytes at 30 days of age; 6 rats made up the intact control group. In histological preparations of different skeletal muscle groups, the width and cross-sectional area of muscle fibers, the area of nuclei, and the number of myocytes and myosatellite cells were evaluated. In the second part of the experiment, 15 intact rats were injected with the studied xenogeneic RNA and the amounts of ribonucleic acids in peripheral blood lymphocytes, spleen lymphocytes, and skeletal muscles were determined 2 hours and 24 hours after injection.Results. After the 40- day physical activity, the width of the fibers and the area of myocyte nuclei in the skeletal muscles increased; the absolute number of myosatellite cells and the area of their nuclei did not change. After administration of xenogenic RNA in the trained rats, in addition to an increase in the thickness and cross-sectional area of muscle fibers, the absolute number of myosatellite cells in m. biceps femoris, in m. triceps brachii, and in m. pectoralis major increased 1.4-fold, 1.3-fold, and 1.4-fold, respectively; the area of myosatellite nuclei increased on average by 7%. In intact rats, two hours after xenogeneic RNA injection, the amount of RNA in skeletal muscles remained unchanged, it increased by 19% in spleen lymphocytes, and by 16% in peripheral blood lymphocytes. At 24 hours, the RNA amount in the lymphocytes remained significantly higher than the control values, while in the muscle tissue, it didn’t differ from the control.Conclusion. Xenogeneic lymphocytic RNA stimulates physiological myogenesis by activating myosatellite cell proliferation.